2015
DOI: 10.1134/s1995425515030038
|View full text |Cite
|
Sign up to set email alerts
|

Biotic indices and metrics in assessment of the water quality of small rivers on the territory of Ergaki Nature Park (South of Krasnoyarsk Krai)

Abstract: This article presents the dominant species and groups and the spatial distribution and structural indices of benthic communities in small mountain streams located on the territory of the Ergaki Nature Park (in the south of Krasnoyarsk krai). A comparative analysis of bioindicators and metrics, a part of which is used by the European Water Framework Directive to determine water quality, was carried out. It was established that the EPT, BMWP, and IBGN indices have the highest sensitivity, which allows one to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The FBI index is inversely related to the quality of water and increases with the pollution of the river. In other hand, low FBI values demonstrate an increase in the number of pollution-sensitive macroinvertebrates and a decrease in tolerant taxa (Andrianova, 2015). In this study, the FBI index represent a response of macroinvertebrate to organic pollutants originate from domestic sewage, urban run-off, industrial effluents and farm wastes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The FBI index is inversely related to the quality of water and increases with the pollution of the river. In other hand, low FBI values demonstrate an increase in the number of pollution-sensitive macroinvertebrates and a decrease in tolerant taxa (Andrianova, 2015). In this study, the FBI index represent a response of macroinvertebrate to organic pollutants originate from domestic sewage, urban run-off, industrial effluents and farm wastes.…”
Section: Discussionmentioning
confidence: 95%
“…Most probably, the impact from organic pollution sources such as intense activity of the leather-making factory, municipal and domestic wastewater had an adverse impact on the composition of macroinvertebrate community. Although these macroinvertebrate based indices have been primarily applied to evaluate the impact of organic pollution and nutrient enrichment that can affect the availability of dissolved oxygen in freshwater ecosystems (Azrina et al, 2006;Sharifinia et al, 2012;Gonzalo and Camargo, 2013;Andrianova, 2015), it should be clear that they can also respond relatively well to the impact of other physico-chemical parameters. This water pollution would be directly responsible for considerable changes in the values of macroinvertebrate based indices (with decreasing in BMWP values, and conversely FBI increasing its values) at sampling sites that located in downstream from the agricultural, industrial, municipal and domestic effluents (especially at S5 and S6).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we found that of all analysed environmental parameters, ammonium ions, orthophosphates, water temperature and water velocity had the strongest impact on the occurrence and density of some taxa. Furthermore, research investigating small watercourses in Europe, which has been conducted, has shown that water temperature and velocity are major determinants of the benthic invertebrate community structure [26][27].…”
Section: Discussionmentioning
confidence: 99%